Identification of Aberrantly Methylated Differentially CpG Sites in Hepatocellular Carcinoma and Their Association With Patient Survival - Guan, Renguo; Guo, Weimin; Hong, Weifeng; Lin, Ye; Zou, Xiongfeng; Shi, Ning; Yang, Dongyang; Zhou, Yu; Jian, Zhixiang; Jin, Haosheng; Lin, Weidong; Yu, Min (Frontiers in Oncology, 2020)
This study aimed to identify aberrantly methylated differentially CpG sites (DMCs) and investigate their prognostic value in hepatocellular carcinoma (HCC). A total of 2404 DMCs were selected from Gene Expression Omnibus (GEO) and validated by the Cancer Genome Atlas (TCGA). The TCGA cohort was divided into a training cohort and a validating cohort.First, the prognostic model based on six DMCs, including cg08351331, cg02910574, cg09947274, cg17589341, cg24652919, and cg26545968, was constructed based on the least absolute shrinkage and selection operator (LASSO) regression Cox analysis. The area under the curve (AUC) of the DMC-based model was 0.765 in the training cohort and 0.734 in the validating cohort. The accuracy of a model combining the DMC signature and American Joint Committee on Cancer (AJCC) stage, with an AUC of 0.795, was better than that of the DMCs or AJCC stage alone. Secondly, further analysis revealed that the methylation rate of cg08351331 was negatively associated with the expression of its relative gene, lipopolysaccharide binding protein (LBP). Besides, the gene expression of LBP was significantly associated with poor overall survival in patients with hepatitis B virus (HBV) infection. Finally, these findings were confirmed by GSE57956 data and our own cohort . In conclusion, we established an accurate DMC-based prognostic model that could be combined with AJCC stage to improve the accuracy of prognostic prediction in HCC. Moreover, our preliminary data indicates that LBP may be a new key factor in HBV-induced HCC initiation through the regulation of its methylation.